Do State and Local Taxes Affect Economic Growth? - Mofidi, Alaeddin; Stone, Joe A. (The Review of Economics and Statistics, 1990)
This paper tests if variations in the treatment of expenditures by state and local governments are an explanation for the inconsistent results of previous tax studies. Estimates for net investment and employment in manufacturing for 1962-82 support this conjecture, indicating that state and local taxes have a negative effect when the revenues are devoted to transfer-payment programs and that (with taxes held constant) increases in expenditures on health, education, consistent with the "vicious circle" phenomenon, do not appear simply to reflect common cyclical movements, and provide evidence of structural linkages implicit in previous results for growth in state personal income. Copyright 1990 by MIT Press.